“Efectividad del método singapur” en la resolución de problemas matemáticos en estudiantes del tercer grado de primaria de una institución educativa privada del distrito de Villa El Salvador. - Delgado Pacheco Marily Rosa (2018)
The primary school student must develop the ability to solve mathematical problems and this implies having pedagogical methods oriented to that goal. The Singapore Method, to promote skills in solving mathematical problems, is based on the CPA (Concrete - Pictorial - Abstract) approach. This method is showing to be effective, since Singapore, by including it in its Mathematics Curriculum, has managed to be among the first positions in the international education ranking PISA (2012). It is an application of pedagogy of mathematics based on research and the pedagogical proposals of Jerome Bruner, Dienes and Skemp, where students, to learn mathematics, progress from the concrete to the pictorial to finally generate abstract representations. In Peru, the results in the PISA evaluations place us in the last positions and this may be due to the lack of a method with evidence of effectiveness for the development of mathematical thinking. Based on the aforementioned, the main objective of this research is to demonstrate the effectiveness of the "Singapore Method" in increasing the level of achievement in solving mathematical problems in third grade students in a private educational institution in the district of Villa El Salvador. A pre-experimental design is used, where the sample is made up of 57 students corresponding to the experimental group who are in the third grade of primary school education, to whom the Singapore Method is applied to work on problem solving and it is used the test of Problem Solving of the Batería Psicopedagógica Evalúa-3 to measure the effectiveness of the method. The results after applying the method, show significant differences in the level of achievement of solving mathematical problems in contrast to the pre-test and post-test applied to the experimental group.